Teaching electromagnetism using interactive-invention instructional strategy and the learning outcome of secondary school students - Ukoh, Edidiong Enyeneokpon (Universitas PGRI Kanjuruhan Malang, 2022)
Electromagnetism is an important aspect of physics in Nigerian secondary school curriculum and has been identified as one of the difficult topics to learn by the students. There seem to be very little research on how to make the learning of electromagnetism easy and enjoyable. Therefore, this study determined the effect of teaching electromagnetism using interactive-invention instructional strategy on senior secondary II (SSII) physics students learning outcome. Pretest posttest control group quasi-experimental research design was employed with 125 SSII students from three randomly selected schools. Intact classes were used and two experimental groups were taught using interactive-invention instructional strategy: group I students worked individually and group II students worked in groups of five and control group was taught conventionally. Two research instruments were used to gather data for the study, namely physics achievement worksheets and in-class interview guide. Students in the experimental groups demonstrated better understanding of the concepts more than those in the control group. In-class interview was carried out at the end of the treatment and all the students in the experimental groups reported that they enjoyed learning the concepts because they had opportunity for hands-on activities and they will prefer that electromagnetic concepts be taught using instructional materials they could manipulate to observe what happens by themselves. It was recommended that teachers use this strategy where hands-on activity-based was emphasized to enhance easy learning of electromagnetism.